PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS VIIIA SMP ISLAM KEPENUHAN - Nur Ilhami; Putri Yuanita; Yenita Roza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The background of this research is the low students’ mathematics test result that is below the minimum criteria of mastery learning (KKM) which percentase 32% on Algebra. This research is a classroom action research which aims to improve the learning process activity and the students’ achievements by applying the cooperative learning STAD method. The subjects of this research was the first semester of VIIIA grade students of SMP Islam Kepenuhan which consist of 10 male and 15 female students. The teacher and students’ activity observation sheets and mathematics test sheets were the instruments used in this research. The observation sheets was analyzed qualitatively to see the improvement of the learning process activity. The mathematics test results were analyzed quantitatively. To see the improvement of the mathematics learning achievement. Based on the analysis, there was improvement in the learning process activity from the beginning of the first cycle until the end of the second cycle. Furthermore, the analysis of the mathematics test results showed the increasing of the number of students who achieve the Standard Criteria Minimum with percentage 40% in the first test and 56% in the second test respectively. That there is improvement of the students’ basic score from the first test to the second test. In conclusion, the application of STAD method can improve the students’ learning process activity and the students’ mathematics test results in the first semester VIIIA grade students of SMP Islam Kepenuhan in academic year 2017/2018.Key Word: Students Math Achievement, Cooperative Learning, Student Team Achievement Division Types, Clasroom Action Research.